Design of a double wishbone front suspension for an orchard–vineyard tractor: Kinematic analysis. (February 2015) - Uberti, Stefano; Gadola, Marco; Chindamo, Daniel; Romano, Matteo; Galli, Francesco
Abstract: This paper deals with the design and implementation of a double wishbone front suspension for a vineyard–orchard tractor, developed in conjunction with a major tractor brand. To date, independent front suspensions are only found on commercial tractors over 150 kW. A front suspended axle is recognized as a popular option in improving tractor ride performance on larger vehicles. Despite their narrow track, vineyard–orchard tractors are required to have good lateral stability and stability on slopes (i.e. at least 28° rollover angle) and an extremely tight turning diameter for a 4WD vehicle (less than 7 m). The discussion is concered with retrofitting an existing vehicle with a double wishbone front suspension. This paper focuses on the layout and kinematic analysis phases of the design process. These were conducted in collaboration with the vehicle manufacturer to demonstrate suspension feasibility in terms of available space and correct kinematic layout. The final kinematic turning diameter obtained is about 6.4 m, with a ±65 mm suspension travel available. The roll centre height value is not very sensitive to steering (about −95 mm excursion in the Z axis from no-steer position to full steer).